Efektivitas Pengendalian Internal, Kepuasan Kerja, dan Kecenderungan Kecurangan Akuntansi - Paranoan, Natalia; Tandungan, Edmondus Sadesto; Sipi, Afian Dezi Sanda (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Tadulako, 2018)
This study aimed to examine the effect of the internal control effectiveness and job satisfaction on the trend of accounting fraud at state-owned enterprises in Makassar. This research conducted at employees of state-owned enterprises. The data collection will be done by using survey through questionnaires taken from state-owned companies in the city of Makassar on 65 respondents and using proportional random sampling. The questionnaire is tested for validity and reliability before collecting research data. Test requirements analysis that includes test instruments and classic assumption test including normality test, test multicoloniarity, heteroscedasticity test and linearity test. Data analysis method is simple regression analysis and multiple regression analysis.